Investigation on in vivo and in vitro blood compatibility of polypyrrole-coated titanium for cardiovascular application. (23rd May 2012) - Fan, Jianping; Xie, Aini; Xia, Chengkun; Liu, Chenggui; Zhang, Kailun
To identify the suitability of a conducting polymer-polypyrrole for development of a surface modification strategy of titanium, we electrocoated the monomer of pyrrole on titanium surface and produced an adherent polypyrrole coating. Then, this coating was characterised in terms of its mechanical and physical properties and also evaluated for in vivo and in vitro blood compatibility. It was found polypyrrole is more compatible than the bare titanium material with blood and possesses superior adhesion strength to titanium substrate and may serve as an ideal platform for anticoagulant functionalisation of titanium surface in the future.